Answer : option C-> B'

Solution:

We have to find f(A,A,B,B) for given f(A,B,C,D)

Hence, replace B with A, C with B, D with B.

Now for first M - The output is A. (i.e when A=1, Mout=1. when A=0, Mout=0) Hence, A

For top M: For two inputs to be 1 B' has to be 1. Since one and always one of A , A' will be 1.

Similarly for bottom M: B has to be 1. (for two inputs to be 1)

Hence , For final M, inputs are B',B' and B. For atleast two inputs to be 1. B' has to be 1.

Hence final f(A,A,B,B)=1, when B' =1.

Hence, Ans- B'